2012
DOI: 10.1007/s10637-012-9841-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of DHP107, a mucoadhesive lipid form of oral paclitaxel, in patients with advanced solid tumors: Crossover comparisons with intravenous paclitaxel

Abstract: DHP107 was safe and feasible in patients with advanced malignancies. As exposure of paclitaxel plateau among patients receiving more than 250 mg/m(2) of DHP107, the dose escalation of DHP107 may be limited to 250 mg/m(2) in further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…CrEL is a well-documented risk factor of hypersensitivity reactions, and CrEL-free formulations do not cause hypersensitivity reactions [3,21,22]. Oral paclitaxel and HM30181A did not induce hypersensitivity reactions without premedication, similar to the other CrEL-free paclitaxel formulations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…CrEL is a well-documented risk factor of hypersensitivity reactions, and CrEL-free formulations do not cause hypersensitivity reactions [3,21,22]. Oral paclitaxel and HM30181A did not induce hypersensitivity reactions without premedication, similar to the other CrEL-free paclitaxel formulations.…”
Section: Discussionmentioning
confidence: 87%
“…The potential advantages of oral formulation include the following: lack of hypersensitivity, convenience for patients, and potential continuous exposure to paclitaxel. Some oral forms of paclitaxel have been developed and exhibited promising results in phase 1 studies [2,3]; however, none of these agents have been fully developed. The major obstacle in developing oral paclitaxel has been poor oral bioavailability that originates from high affinity for P-glycoprotein (P-gp), which is abundant in the gastrointestinal mucosa [4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a novel oral formulation of paclitaxel called DHP107 was developed that does not require co-administration of Cyclosporine A. DHP107 is a mucoadhesive formulation of paclitaxel, created by dissolving paclitaxel in a mixture of monoolein, tricarprylin and Tween ® 80 [5]. One Phase I crossover study has been completed using DHP107 in patients with advanced solid tumor malignancies who had failed standard therapies [6]. In total, 33 patients were enrolled and given DHP107 once and then subsequently received iv.…”
Section: Novel Oral Formulations Of Paclitaxel and Docetaxelmentioning
confidence: 99%
“…Pharmacokinetics showed that inter-patient variability increased greatly above doses of 250 mg/m 2 and the authors of the study recommended this as the maximum dose for future studies. Another Phase I trial of DHP107 using a weekly dosing schedule is in progress [6]…”
Section: Novel Oral Formulations Of Paclitaxel and Docetaxelmentioning
confidence: 99%
“…In a previous first-in-human study, a single escalating dose of oral DHP107 was shown to be safe and feasible, with no doselimiting toxicity when administered at up to 600 mg/m 2 in patients with advanced solid tumors [21,22] . In a phase I study, the recommended oral dose of DHP107 has been reported to…”
Section: Introductionmentioning
confidence: 99%